2016
DOI: 10.1002/aic.15508
|View full text |Cite
|
Sign up to set email alerts
|

Preparation of thin film nanocomposite membranes with surface modified MOF for high flux organic solvent nanofiltration

Abstract: Preparation of defect‐free and optimized thin film nanocomposite (TFN) membranes is an effective way to enhance the process of organic solvent nanofiltration. However, it still remains a great challenge due to poor filler particle dispersibility in organic phase and compatible issue between fillers and polymers. Aiming at these difficulties, UiO‐66‐NH2 nanoparticles were surface modified with long alkyl chains and used in the preparation of TFN membranes. As a result, defect‐free TFN membranes with ultrathin M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
59
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 123 publications
(59 citation statements)
references
References 48 publications
0
59
0
Order By: Relevance
“…And the new absorption peak at 1033 cm À1 was ascribed to C-C stretching vibration of palmitoyl chloride. 16 These 3 new absorption peaks indicated that the surface of UiO-66-NH 2 was successfully modied by palmitoyl chloride.…”
Section: Characterization Of Uio-66-nh 2 and Uio-66-nh 2 -Pcmentioning
confidence: 98%
See 1 more Smart Citation
“…And the new absorption peak at 1033 cm À1 was ascribed to C-C stretching vibration of palmitoyl chloride. 16 These 3 new absorption peaks indicated that the surface of UiO-66-NH 2 was successfully modied by palmitoyl chloride.…”
Section: Characterization Of Uio-66-nh 2 and Uio-66-nh 2 -Pcmentioning
confidence: 98%
“…In order to increase the dispersibility of nanoparticles in organic phase, the surface of nanoparticles needed to hold the character of nonpolarity, low surface energy so as to increase the compatibility with organic solvent owing to the nonpolar intrinsic character of organic phase. 16,29 The modication of UiO-66-NH 2 by palmitoyl chloride could increase the compatibility between UiO-66-NH 2 and cyclohexane due to the existence of nonpolar alkyl which possessed the similar character of hexane, and thus UiO-66-NH 2 -PC could get good dispersibility. But it was for this reason that the hydrophilicity of the modied nanoparticles declined.…”
Section: Characterization Of Uio-66-nh 2 and Uio-66-nh 2 -Pcmentioning
confidence: 99%
“…The presence of the alkyl chains reduces nanoparticle aggregation. A study conducted by Guo et al [53], where nanoparticles were added to the TMC solution in hexane, confirmed the desired effect of this type of nanomaterial. The material maintained almost 100% tetracycline retention, and nearly 30% higher membrane permeability was achieved compared to the unmodified membrane [53].…”
mentioning
confidence: 81%
“…They can be facilely prepared by embedding porous fillers into a polyamide thin film by interfacial polymerization. Since the pioneering work of Sorribas et al on MOF‐based TFN membranes for the separation of methanol and tetrahydrofuran from styrene oligomers, a great number of MOF and COF based ultrathin membranes have been prepared for diverse applications, including OSN, desalination, dye removal, gas separation, etc. Very recently, Xie et al developed a bottom‐up approach to prepare a novel type of MMMs by depositing an ultrathin (≈30 nm), continuous, and defect‐free polymeric membrane on a coarse MOF gutter layer that grows on anodic aluminium oxide (AAO) supports ( Figure ) .…”
Section: Novel Trends In Mmmsmentioning
confidence: 99%